Indole-3-Carboxaldehyde Restores Gut Mucosal Integrity and Protects from Liver Fibrosis in Murine Sclerosing Cholangitis - D’Onofrio, Fiorella (Cells, 2021)
Primary sclerosing cholangitis (PSC) is a long-term liver disease characterized by a progressive course of cholestasis with liver inflammation and fibrosis. Intestinal barrier dysfunction has been implicated in the pathogenesis of PSC. According to the “leaky gut” hypothesis, gut inflammation alters the permeability of the intestinal mucosa, with the translocation of gut-derived products that enter the enterohepatic circulation and cause hepatic inflammation. Thus, the administration of molecules that preserve epithelial barrier integrity would represent a promising therapeutic strategy. Indole-3-carboxaldehyde (3-IAld) is a microbial-derived product working at the interface between the host and the microbiota and is able to promote mucosal immune homeostasis in a variety of preclinical settings. Herein, by resorting to a murine model of PSC, we found that 3-IAld formulated for localized delivery in the gut alleviates hepatic inflammation and fibrosis by modulating the intestinal microbiota and activating the aryl hydrocarbon receptor-IL-22 axis to restore mucosal integrity. This study points to the therapeutic potential of 3-IAld in liver pathology.